Dermoscopic findings in a patient with multiple piloleiomyomas - Francisco Macedo Paschoal (Mattioli1885, 2012)
Piloleiomyoma can manifest itself as a pigmented lesion and part of the differential diagnosis with other pigmented skin lesions. However, we are not aware of previous descriptions in the literature of the dermoscopic features of piloleiomyoma. This article describes the dermoscopic findings observed in a patient with multiple piloleiomyomas. On dermoscopic evaluation, piloleiomyoma has characteristics similar to dermatofibroma with a thin peripheral pigmented network and central scar-like area. Some of the piloleiomyomas analyzed in this patient also presented with hyperpigmented circular and/or elongated structures within the central hypopigmented area.